Reflection Online Learning During Pandemic and New Normal: Barriers, Readiness, Solutions, and Teacher Innovation - Wakhidah, Nur; Erman, Erman; widyaningrum, Astri; Aini, Vera Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to reflect online learning when Covid-19 spread include what happened, how obstacles, teacher readiness, solutions, and teacher innovations to improving learning. The mixed-method research was conducted on 30 SD/MI and SMP/MTs teachers in various fields. Data collection was carried out by survey using google form and interviews. Teacher readiness data is calculated quantitatively using percentages. Qualitative data (constraints, solutions, and innovations) were analyzed qualitatively. The results showed barriers to online learning came from teachers, schools, students, and material content; The percentage in new normal teacher readiness to do online learning is 73,49 (moderate category); Solutions in form of improving online learning infrastructure, providing quotas, teachers not only assigning tasks but activities, improving teacher skills in the field of IT. Teacher innovation is planning blended learning in the new normal and designing learning using internet applications, and empowering teacher working groups. The results of reflection show that online learning which is done suddenly produces many obstacles. Online learning planning needs to be done by improving teacher skills in the internet technology field, providing online learning facilities and infrastructure, understanding the characteristics of the material, and familiarizing students with technology following global demands. For this reason, it is necessary to initiate blended learning, namely a combination of online and face-to-face in facing global challenges.